Clinical Relevance of Brain Atrophy Measures in Multiple Sclerosis - Uher, Tomáš (Karolinum Press, 2023)
Magnetic resonance imaging of the brain and spinal cord in patients with multiple sclerosis is crucial for diagnosis as well as monitoring and predicting disease activity. Comprehensive MR measurements including assessment of brain and spinal cord volume changes have the potential to improve patient monitoring, allow earlier detection of subclinical disease activity, and identify patients with depleted brain reserve who are at highest risk of disability progression. Cerebral atrophy measurements are now a secondary outcome of many clinical trials, although their wider use in routine clinical practice is still hampered by some technical limitations. However, evidence from clinical practice shows that assessment of brain and spinal cord volume change is feasible and has the potential to improve patient treatment.